Health Education About Clean and Healthy Living Behavior (PHBS) To Increased Knowledge of School Age Children: Systematic Review - Sasmitha, Nur Ridha; Hasnah; Sutria, Eny (Journal Of Nursing Practice, 2020)
Background: In school-age children, the most common problem is clean and healthy living behavior, one way to improve clean and healthy living behavior by providing health education.Purpose: This study aimed to identify and analyze available scientific evidence about the effectiveness of health education on improving the knowledge of school-age children.Methods: This research method uses quantitative descriptive design with systematic review approach. Literature search through database: Google Scholar, Garuda Portal, Indonesian Scientific Journal Database and International Journal of Social Science and Humanity with structured research questions using keywords using the PICO method (Patient, Intervention, Comparison of Intervention and Outcome).Results: There were 83 articles identified, only 6 that met the inclusion criteria were analyzed using Duffy's Research Appraisal Checklist Approach.Conclusion: Health education with the media is very effective in increasing the knowledge of school-age children about PHBS, the media obtained from a variety of literature, namely education with snakes and ladders, quiz games, pocket book media, video media, poster methods, and dance video methods. Health Education with the media is very effective in increasing the knowledge of school-age children found in this review to be used as an intervention in health education